Financial and non-financial as welfare incentives on job satisfaction among public secondary school teachers in Oyo, Oyo State, Nigeria (2024)
This study examined financial and nonfinancial as welfare incentives on job satisfaction among public secondary school teachers. This study utilized a descriptive research design while a simple sampling technique was used to select 225 public secondary school teachers. A self-constructed instrument was used to gather relevant data. Three research hypotheses were formulated while Pearson Product Moment Correlation was used to analyze the hypotheses. Findings revealed that there is shows that there is significant relationship between financial and job satisfaction among public secondary school teachers in Afijio local government area (r = .0.621, n=255, p (.013) <.05), there is a significant relationship between significant relationship between nonfinancial incentives and job satisfaction among public secondary school teachers in Afijio local government area (r = .210, n=255, p (.036) <.05). Furthermore, there is a joint significant relationship between financial/ nonfinancial incentives and job satisfaction among public secondary school teachers in Afijio local government area. The study concluded that financial and nonfinancial incentives significantly influenced job satisfaction among teachers. Therefore, it was recommended among others that education stakeholder should make use of both financial and nonfinancial incentives to improve the organization productivity and job satisfaction.